Estimation of salivary glycoconjugates and salivary ros levels in chronic periodontitis: a clinico-biochemical study - Roy, Jenny Susan; Manjunath, Nandini; Bhat, Kishore; George, Anjana Mary; Nishana, Fathimath; Mathew, Lia (International Journal of Research in Medical Sciences, 2017)
Background: Periodontitis is a chronic inflammatory disease of periodontal tissue, characterized by persistent inflammation of the connective tissue and alveolar bone destruction. Patients with periodontal disease show the differences in the composition of saliva. Newer diagnostic tools based on analysis of body fluids such as saliva, GCF and serum are found to be useful for diagnosis as well as monitoring the disease activity. Thus, aim of the study was to estimate the concentration of salivary glycoconjugates (sialic acid, total protein) and salivary ROS in unstimulated whole saliva of subjects with chronic periodontitis and to compare the concentration with healthy/gingivitis subjects. Methods: The study sample consisted of 60 subjects (33 males and 27 females) with age ranging from 30-60 years. A detailed case history was taken from all the subjects and periodontal disease parameters (bleeding on probing, probing pocket depth and clinical attachment levels) were recorded at baseline and subjects were divided into 2 groups. Group I- control group (healthy/gingivitis subjects) and Group II -test group (chronic periodontitis). Saliva samples were collected from the subjects and stored at -700 ºC. Periodate Resorcinol Assay was done to estimate the levels of sialic acid, Biuret test was done to assess the levels of total protein and d-ROMs test was done to assess the level of ROS. Statistical analysis was done using students unpaired ‘t’ test and Pearsons correlation test. Results: It was found that the levels of salivary glycoconjugates and ROS are increased in subjects with chronic periodontitis when compared to healthy/gingivitis subjects. Thus it can reflect the clinical status of gingival and periodontal tissues. Conclusions: Estimation of the levels of glycoconjugates and ROS may be used as one of the reliable biomarkers to assess the severity of periodontal disease and to monitor the disease progression.